2020
DOI: 10.1108/jmtm-10-2019-0382
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of enablers on the successful implementation of green manufacturing for Irish SMEs

Abstract: PurposeThe purpose of this study is to identify a comprehensive list of main enablers of successful implementation of green manufacturing (GM) practices in small and medium-sized enterprises (SMEs). Based on the inputs from Irish SMEs' experts, a validated conceptual hierarchy model of the identified enablers is developed to analyse and prioritise the most dominant ones.Design/methodology/approachData were collected using a questionnaire survey responded by various professionals in Irish manufacturing SMEs. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 54 publications
10
59
0
1
Order By: Relevance
“…The definitions of SMEs vary among countries and predominantly dominated by the stage of economic development of a particular country (Deshmukh and Chavan, 2012). Therefore, following previous studies (Ghadimi et al , 2020; Mishra, 2016), we adopted the local definition of SMEs in China. According to the official classification in China, we defined a “manufacturing SME” as a firm with fewer than 1,000 employees and sales revenue of less than 400m RMB.…”
Section: Methodsmentioning
confidence: 99%
“…The definitions of SMEs vary among countries and predominantly dominated by the stage of economic development of a particular country (Deshmukh and Chavan, 2012). Therefore, following previous studies (Ghadimi et al , 2020; Mishra, 2016), we adopted the local definition of SMEs in China. According to the official classification in China, we defined a “manufacturing SME” as a firm with fewer than 1,000 employees and sales revenue of less than 400m RMB.…”
Section: Methodsmentioning
confidence: 99%
“…Ghadimi et al (2020) presented a seminal work on the analysis of enablers of successful implementation of Green Manufacturing for Irish firms. The study systematically identified internal and external enablers of green manufacturing.…”
Section: Literature Review and Hypothetical Modelmentioning
confidence: 99%
“…Moreover, the interactive effect of GHRM and green organizational culture is a topic of great relevance in today's scholarship (Jackson et al , 2011). A recent study by Ghadimi et al (2020) identified organizational culture as a key driver of green manufacturing. Nevertheless, GHRM scholars have not looked into the green culture from the point of view of its enablers.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing has been playing a pivotal role in generating employment and improving national economies ever since the industrial revolution (Islam and Karim, 2011;Duflou et al, 2012;Shukla and Adil, 2021). This trend is likely to continue due to an increased demand of goods by the world's ever-growing population (Eastwood and Haapala, 2015;Ghadimi et al, 2020). Nonetheless, advancements in the manufacturing sector have had its adverse effects on our planet in the form of global warming, resource depletion and local waste disposal and related catastrophes (Sangwan, 2011;Famiyeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2008) portrayed GM as "an imperative manufacturing strategy for the twenty-first century, integrating all the issues of manufacturing with its ultimate goal of minimizing environmental impact and resource consumption." In other words, GM should incorporate green product design, green technology, green production and environmentally safe disposal, products (Belhadi et al, 2020;Afum et al, 2020;Ghadimi et al, 2020;Yildiz and Sezen, 2019). Today, there is clear evidence that a growing number of manufacturing firms are moving to GM (Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%